PERANGKAT LUNAK PENGARSIPAN SURAT MENYURAT BERBASIS WEB DALAM UPAYA MENINGKATKAN PELAYANAN ADMINSTRASI - Nyimas Sopiah; Indri Wahyuni (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Correspondence is very important in managing an organization. With correspondence, the administrative process of an organization will be neater making, so that it is expected that all records can be arranged properly. This study aims to provide a computer-based letter management system consisting of the process of managing bid letters, payment letters and contract letters and making report management letters more efficiently and effectively. The system development method used is the Web Engineering. Design tools using UML (Unified Modelling Language)-Based Web Engineering (UWE). This software was built using VB.Net. The benefit of this research is to increase an understanding and insight in the world of work that computer science will facilitate work in a company from any matter, for example, one example letter making and archiving